The Impact of Chemotherapy on Physical and Psychological Conditions in Patients with Nasopharyngeal Cancer at PKU Muhammadiyah Gombong Hospital: Dampak Kemoterapi terhadap Kondisi Fisik dan Psikis pada Pasien Ca Nasofaring di RS PKU Muhammadiyah Gombong - Cahyanti, Putri Nur; Santoso, Dadi (Prosiding University Research Colloquium, 2023)
Background: Ca nasopharynx is a malignant tumor that grows in the Rosenmuller tissue of the nasopharynx and upper part of the nasopharynx. One of the treatments performed by KNF patients is chemotherapy. This therapy causes side effects for patients physically and psychologically. Physical side effects such as alopecia, decreased appetite, nausea and vomiting. While psychologically such as depression, anxiety, and stress. Objective: To determine the impact of chemotherapy on ca nasopharynx patients at PKU Muhammadiyah Gombong Hospital. Methods: This study was a descriptive study with cross-sectional approach. Sampling in accordance with the sample criteria set by the researcher, as many as 45 respondents became respondents with total sampling technique. Results: The results of this study were dominated by male gender 29 respondents (64.4%), 21 respondents aged 41-60 years (46.7%), the last high school education as many as 18 respondents (40%), 13 respondents worked as self-employed (28.9%), long suffering from KNF <1 year as many as 19 respondents (42.2%), 24 respondents underwent the 4th chemotherapy cycle (53.3%). The impact of chemotherapy based on physical conditions was mostly categorized as moderate 30 respondents (66.7%). Based on psychological conditions at the level of depression of respondents with mild categories as many as 16 respondents (35.6%), at the level of anxiety as many as 20 respondents (44.4%), while the level of stress in the moderate category was 22 respondents (48.9%). Conclusion: The impact of chemotherapy on physical conditions is mostly categorized as moderate. While the psychological condition is divided into 3 levels, including mild depression, moderate anxiety, and moderate stress. Recommendation: Future researchers are expected to examine the Factors Affecting Physical and Psychic Conditions in Chemotherapy Patients with Nasopharyngeal Ca.